Adenovirus type 2 assembly analyzed by reversible cross-linking of labile intermediates. - D'Halluin, J C (1978)
Dimethyl-4,4'-dithiobisbutyrimidate dihydrochloride was used as a cleavable cross-linking reagent to maintain the structure of labile intermediates in adenovirus type 2 assembly. Analysis on sucrose gradients of nuclear adenovirus particles revealed two size classes, with sedimentation rates of 750 and 600S. After reversible fixation with diimido ester, the different classes were further separated on CsCl gradients and characterized with regard to their buoyant density, DNA content, and polypeptide composition. The 750S particles banded at 1.345 g/cm3 in CsCl, contained a DNA with a sedimentation coefficient of 34S in alkaline sucrose gradients, and had a polypeptide composition similar to that of young virions. The 600S population consisted of two types of particles with buoyant densities of 1.315 and 1.37 g/cm3. The 1.315-g/cm3 particles contained a DNA fragment of 7--11S and lacked the core proteins V and VII. In their place were found precursors P VI and P VIII and two nonvirion proteins with molecular weights of 50,000 (50K) and 39,000 (39K). 34S DNA was present in the 1.37-g/cm3 particles, which also lacked core proteins V and VII, as well as the 50K and 39K. Pulse-chase labeling kinetics suggested that the 1.315-g/cm3 particles were anterior to the 1.37-g/cm3 particles, themselves preceding the 1.345-g/cm3 young virions, and that the release of both 50K and 39K, possible scaffolding proteins, was required for entry of viral DNA.